Análise do efeito da inundação e estrutura da vegetação sobre a riqueza e distribuição da assembleia de formigas edáficas, estudo comparativo entre áreas inundáveis e não inundáveis na região norte do Pantanal - Meurer, Eliandra (2015)
This study evaluated the effect of periodic flooding and habitat structure on the richness and distribution of the soil ant assemblage in a comparative study of floodprone areas (grassland, mounds and landizais fields), non flooded areas (ridges and cerrado) in the Northern region of the Pantanal, based on the following items: (i) what is the richness of soil ants occurring in this region? (ii) what is the influence of periodic flooding as to the richness and distribution of soil ant community, comparing flooded and non flooded areas in region north the Pantanal? and (iii) what is the effect of vegetation structure on the distribution and richness of soil ant assemblage in region north the Pantanal? The results of this research indicate that the northern region of the Pantanal has a wide richness of species of soil ants and can be compared to ant richness in areas of the Cerrado, the Atlantic Forest. The registration of four new species of ants for this region indicates that the richness found in this environment is probably higher, highlighting the need to continue these studies. It was observed that the ants move from the wetlands to non flooded areas during the aquatic phase of the Pantanal, where they remain throughout the flood period, returning to their habitats of origin during the low water period. This move causes the structuring of the assemblage in mosaics with specific compositions in both the studied areas. The structural variation in the Pantanal vegetation types (range, savannah, landizal, carvoal, mound field, and grassland) influences directly the distribution of the ant assemblage. The percentage of sand and the accumulation of litter were significant factors in the distribution of the soil ant assemblage in this region, forming different groups among the studied areas. The flood rates and structural change in the vegetation, characteristic of the Pantanal, provide a wide range of habitats and resources which are necessary for soil ants over the seasonal period to which the region is subject, generating assemblage with distinct patterns and dynamics in each type of habitat in this flooded ecosystem.